A cultural history of causality : science, murder novels, and systems of thought - Kern, Stephen (Princeton University Press, 2004)
This pioneering work is the first to trace how our understanding of the causes of human behavior has changed radically over the course of European and American cultural history since 1830. Focusing on the act of murder, as documented vividly by more than a hundred novels including Crime and Punishment, An American Tragedy, The Trial, and Lolita, Stephen Kern devotes each chapter of A Cultural History of Causality to examining a specific causal factor or motive for murder--ancestry, childhood, language, sexuality, emotion, mind, society, and ideology. In addition to drawing on particular novels.